Taguchi Method Based Approach for Improvement in Mechanical Properties of Fly Ash Reinforced Aluminum Matrix Composites - Paras (My University, 2014)
Conventional monolithic materials such as aluminium and magnesium are lightweight and have certain properties that give them an edge over their counterparts i.e. iron and steel. But, they do not have the strength requirements necessary for several applications. The main characteristics possessed by aluminium are: low density, good resistance to corrosion, low thermal expansion, and established casting techniques for mass production. The attractive characteristics possessed by these materials forced scientist to do research for enhancing their properties and making these suitable to be used in high end applications, such as automotive and aerospace. As a result of these requirements, invention of MMCs (Metal Matrix Composites) had taken place. Advances in the science of MMCs present scientists with an opportunity to design light-weight aluminum based materials with precise balances of mechanical and physical properties. Furthermore, the MMCs manufactured by dispersing coal fly ash in common aluminum alloys is found to be the most economical method to improve mechanical and physical properties. Mechanical properties of composites are affected by the size, shape and volume fraction of the reinforcement, matrix material and reaction at the interface. Matrix / reinforcement interface has a major role to play in relation to the mechanical properties of the composites. In this work, an attempt has been made to determine the influence of volume fraction of fly ash, addition of magnesium (wetting agent) and the effect of stirrer speed on the mechanical properties of MMCs produced by stir casting method. Optimum values of these are identified for attaining better wear resistance, hardness and tensile strength of composites by the application of Taguchi method and Analysis of Variance (ANOVA).
Master of Engineering
Keywords: Metal Matrix Composites; Analysis of Variance; stir casting; flyash; magnesium; aluminium; mechanical engineering